Dietary choline is related to neural efficiency during a selective attention task among middle-aged adults with overweight and obesity. (3rd April 2021) - Edwards, Caitlyn G.; Walk, Anne M.; Cannavale, Corinne N.; Flemming, Isabel R.; Thompson, Sharon V.; Reeser, Ginger R.; Holscher, Hannah D.; Khan, Naiman A.
ABSTRACT: Objectives: Obesity is associated with poorer brain health and cognitive function. However, it is not clear whether specific dietary factors may provide neuroprotective effects among individuals with overweight and obesity. The aim of this study was to examine the impact of choline intake on neurophysiological markers of attentional control among young and middle-aged adults with overweight or obesity. Methods: 146 adults with BMI ≥25 kg/m 2 (34.0 ± 5.9 years, 57 males) participated in the study. Behavioral performance (accuracy and reaction time) and neuroelectric indices (event-related brain potentials [ERPs]) of attentional inhibition were assessed during a Flanker task. Specifically, the amplitude and latency of the P3 waveform in a central-parietal region of interest (ROI) were used to index attentional resource allocation and information processing speed, respectively. Choline intake and overall diet quality (Healthy Eating Index [HEI-2015]) were assessed using 7-day diet records. Intelligence Quotient was assessed using the Kaufman-Brief Intelligence Test. Regression analyses were conducted to examine the relationship between habitual dietary choline intake and cognitive outcomes following adjustment of demographic factors, IQ, HEI-2015, and BMI. Results: Choline intake was selectively associated with a lower peak amplitude of the P300 waveform during incongruent trials ( β  = −0.25, p  = <0.01). No significant relationships were observed for accuracy or reaction time. Discussion: Higher choline intake is associated with more efficient neural processing among adults with overweight and obesity. Intervention are necessary to determine whether choline consumption provides neuroprotective effects for executive function among individuals with elevated weight status.